PENGARUH PENGGUNAAN NEBACETIN BUBUK TERHADAP TERJADINYA PLEBITIS DI RUMAH SAKIT STELLA MARIS MAKASSAR - Sr Anita Sampe (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2018)
Plebitis is the venous inflammation caused by a variety of factors such as chemical, mechanical and bacteria, as a result of intravenous therapy. The occurrence of cases of plebitis resulted in such a huge impact for patients such as the addition of day care, and increased maintenance costs for hospitals would lose the quality of hospital services. See the impact will happen then takes the role of health workers, especially in the prevention of drug prophylaxis be plebitis i.e. nebacetin powder. The purpose of this research is to analyze the effect of the use of nebacetin powder against the onset of plebitis. This type of research is observational Cohort Study with analytic approach. The population in this research is all of a patient's intravenous therapy will be installed and will be undergoing treatment in the Hospital of Stella Maris with Accidental Sampling sampling technique, where the sample is determined by the researcher then uses the criteria of inclusion and exclusion so as to get the 54 respondents. Engineering data collection using the observation sheet. The results of this research are processed by using the Relative Risk analysis test which is read on the value of RR. Obtained a value of RR = 2.3 Ha received meaningful Ho denied that means when not using nebacetin the powder at risk for experiencing plebitis 2.3 times than using a nebacetin powder. Thus in intravenous therapy should be given the drug nebacetin powder to reduce the likelihood of the occurrence of plebitis and improve the quality of service of hospital and recommended it to the nurse to know this as a basic science in the infusion.